Konsepsi Bangun Perusahaan Koperasi: Kerangka Pemikiran Badan Usaha Yang Ideal Menurut Pasal 33 Ayat (1) UUD 1945 - Pulungan, M. Sofyan (UI Scholars Hub, 2019)
Co-operative as company structure (bangun perusahaan) is a concept developed by the Founding Fathers, enshrined in Article 33.1 of the 1945 Constitution. This concept is further developed by renowned economists and lawyers as well. This Article explores the thoughts of Mohammad Hatta, Soepomo, economists and lawyers who have contributed to the development of the concept of co-operatives as company structure. Subsequently, it will offer a framework in which the constitutional stipulation of